PENGARUH CORPORATE SOCIAL RESPONSIBILITY (CSR) LINGKUNGAN DAN RASIO PROFITABILITAS TERHADAP NILAI PERUSAHAAN SUBSEKTOR OIL, GAS, DAN COAL DI BURSA EFEK INDONESIA (BEI) TAHUN 2021-2024 - M. Dedy Eko Trisyono Safari; Nuzilatul Fithriyah; Hevi Susanti (Universitas Merdeka Madiun, 2026)
This study aims to examine the effect of environmental Corporate Social Responsibility (CSR) and profitability on firm value in the oil, gas, and coal sub-sector companies listed on the Bursa Efek Indonesia (IDX) during the 2021–2024 period. The independent variables consist of environmental CSR measured using the GRI environmental indicators and profitability measured by Return on Assets (ROA), while firm value as the dependent variable is measured by Price to Book Value (PBV). The sample was selected using purposive sampling, resulting in 14 companies out of 64 population firms. The results show that, partially, environmental CSR does not have a significant effect on firm value, whereas profitability has a positive and significant effect on firm value. Simultaneously, environmental CSR and profitability have a significant effect on firm value. These findings indicate that investors tend to place greater emphasis on financial performance than on environmental CSR disclosure when assessing firm value